Note on Ground States of Nonlinear Schrodinger Systems (Journal of Partial Differential Equations, 2006)
We give sufficient and necessary conditions for the existence and nonexistence of positive ground state solutions of a class of coupled nonlinear Schrödinger equations.
Keywords: Ground states; Schrödinger systems